Microbiological Study of Male ’ s Urethral Discharge - AL – Obadi, Waleed I A (AL-Kindy College Medical Journal, 2007)
Objective: To evaluate male patients complaining of urethritis clinically according to the isolated organisms. Method: A total of 100 male patients attending to of Dermatological and Venereal private clinics for the period April 2003 to November 2003 were included in the study. Urethral swab was obtained from each male for culture and direct immunofluorescence examination was done. Demographic data was obtained, also. Results: N. gonorrhoea was the predominate cause of infection in 22%. A peak of infection was reported in the second decade of age. Highest rate reported among single males. A significant association was noticed between profuse discharge and infection with gonorrhoea. Conclusion: This study demonstrated that peak of infection in the second decade of age and among singles. A broad range of causative agents was reported.